Quantification of Vasa Vasorum Density in MSCT Coronary Angiograms – Role of CT-Image Voxel Size - Moritz, Regina (2010)
OBJECTIVE: This study is motivated by the possibility of using CT to detect early coronary atherosclerosis by the increased CT-values within the arterial wall resulting from vasa vasorum proliferation. METHODS: Coronary arteries (n=5) with early atherosclerotic changes were injected with Microfil(®) and scanned (micro-CT). Noise was added to the scan projection data sets (to represent the radiation exposure of current clinical CT-scanners), and then reconstructed to generate 3D-images at different voxel sizes. RESULTS: Higher CT-values were detected due to contrast agent in vasa vasorum if voxel size was less than (150μm)(3). Contrast in the main lumen increased CT-values dramatically at voxels greater than (100μm)(3), whereas CT-values of the same specimen without contrast in the main lumen remained constant. CONCLUSION: Voxel sizes < (200μm)(3) are needed to quantitate arterial wall opacification due to vasa vasorum proliferation.